Bias by gender: exploring gender-based differences in the endorsement of ADHD symptoms and impairment among adult patients - Platania, Noemi M.; Starreveld, Daniëlle E. J.; Wynchank, Dora; Beekman, Aartjan T. F.; Kooij, Sandra (Frontiers in Global Women's Health, 2025)
BackgroundResearch on adult attention-deficit/hyperactivity disorder (ADHD) remains limited, particularly regarding the experiences of women.MethodsThis exploratory study investigates patient responses to the Diagnostic Interview for ADHD in Adults (DIVA-5), which assesses current (adult) and retrospective (childhood) ADHD symptoms based on criteria from the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). We focused on overall endorsement rates of ADHD symptoms, impairments, and specific examples of both, with particular attention to gender differences. Using descriptive statistics and chi-square tests, we analysed existing DIVA-5 data from 2,257 adult patients diagnosed with ADHD at mental health clinics affiliated with the Parnassia Groep in the Netherlands.ResultsOur findings indicate that ADHD manifests similarly across men and women, though subtle differences in symptom and impairment patterns emerged. Women more frequently endorsed several inattentive and hyperactive/impulsive symptoms in adulthood, whereas men reported higher endorsement rates of several childhood symptoms. Regarding impairments, gender-specific patterns were observed in areas such as self-esteem and social relationships.ConclusionWhile these differences were small, they highlight the need for further investigation into gendered ADHD manifestations. Additionally, we discuss potential measurement limitations and propose recommendations for refining the DIVA-5 and advancing research on gender differences in ADHD.